If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 6y = 17 Solving -6x + 6y = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. -6x + 6y + -6y = 17 + -6y Combine like terms: 6y + -6y = 0 -6x + 0 = 17 + -6y -6x = 17 + -6y Divide each side by '-6'. x = -2.833333333 + y Simplifying x = -2.833333333 + y
| (119+x)/3=62 | | 8s+(-3t)=37 | | 49/x+11=18 | | (58+61+x)/3=62 | | 4x+28=14x-42 | | 6x+5y=26 | | 15s+52-7s=-5s | | 10x-3=2y | | 4(2x-10)=48 | | 13x=150+8x | | 3x-5(-4x-4)=-164 | | y^2-y-12/16-y^2 | | 5/2x+8/x | | 5x+31=73+3x | | 4(2y-5)=12 | | 7(g-4)=4 | | x*8+20=x*4+84 | | 4x^2+200x+4800=0 | | 2x+7(-2x-15)=-33 | | 0.40x-5=23 | | 61-4x=23x+22 | | -55=49x | | x/2+1/2+x/4-3/4=2 | | -8x+4=26x+1 | | 6-7x=61-42x | | (x+4)(x-12)=x(x-9) | | 3(x-7)-4=-19 | | 10x+15-20x=5 | | -68-6x=9x+17 | | w+(w+10)+50=180 | | 44-5x=4x+21 | | 10a-14+6=-12 |